THE EFFECT OF THE PARACHUTE STRATEGY ON FUTURE THINKING AMONG MIDDLE SCHOOL STUDENTS IN HISTORY - Lecturer Fouad Hamid Majeed (Scholars Digest Publishing, 2025)
The goal of identifying the effect of the parachute strategy on future thinking among middle school students in history. To achieve the research goal, the researcher adopted an experimental design with a post-test for two equal groups. The groups were equalized by intelligence, previous achievement, and previous knowledge. The sample consisted of (66) students. There were (32) students for the experimental group and (34) students for the control group. A future thinking test was constructed for second-year intermediate students. Validity and reliability were extracted and were good, and appropriate statistical methods were used.
Keywords: Parachute strategy, future thinking.